2020
DOI: 10.4148/2572-1836.1074
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social networks, mental health, and sobriety on exercise within a collegiate recovery community

Abstract: Exercise is especially beneficial for individuals recovering from addiction. In addition to improved physical, emotional, and mental health, exercise is linked to long-term recovery for those overcoming addiction. With nearly 10% of college students in recovery, and many utilizing campus resources such as collegiate recovery communities (CRCs) to support their recovery, it is important to understand the relationship between exercise and the recovery process among college students. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Thus, it is unsurprising that group-exercise members would report similar compulsive exercise scores as their direct connections. This finding is also supported by previous SNAs that demonstrated similarities in exercise behavior across social ties (Aral and Nicolaides, 2017; Patterson et al , 2020b). Further, it is possible that social expectations and norms within fitness communities translate to shared feelings of guilt when classes are missed or performance is not optimal.…”
Section: Research Question 2: Do Members Of Group-exercise Network Ha...supporting
confidence: 87%
“…Thus, it is unsurprising that group-exercise members would report similar compulsive exercise scores as their direct connections. This finding is also supported by previous SNAs that demonstrated similarities in exercise behavior across social ties (Aral and Nicolaides, 2017; Patterson et al , 2020b). Further, it is possible that social expectations and norms within fitness communities translate to shared feelings of guilt when classes are missed or performance is not optimal.…”
Section: Research Question 2: Do Members Of Group-exercise Network Ha...supporting
confidence: 87%
“…Similarly, in egocentric network research, an investigator might ask respondents to indicate anyone in their life they would trust with a personal matter, eliciting a set of dyads meaningful to each respondent. 28,29 Either way, the name generator creates sets of dyads that make up a network and allow for social network analyses to be conducted. 25 Egocentric and whole network research have been used to demonstrate the importance of social relationships relative to PA. For example, a recent review of SNA studies investigating adolescent PA found social selection and social influence were significantly related to adolescent PA behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…25 For example, researchers conducting whole network research might provide a roster of all members of a network to each respondent, and ask for them to indicate anyone in their defined network they would trust with an important, personal matter. 28 In this case, while respondents are limited to nominating only others in their network, the name generator returns a set of dyads that exist within that network. Similarly, in egocentric network research, an investigator might ask respondents to indicate anyone in their life they would trust with a personal matter, eliciting a set of dyads meaningful to each respondent.…”
Section: Introductionmentioning
confidence: 99%
“…Within our data, “Asking for advice” emerged as the primary theme from Reddit data, suggesting social media could serve as a place for support and information-seeking for people struggling with addiction. Previous research has established the importance of social support for people recovering from SUD [ 9 , 13 , 43 ], and advice seeking is one way to receive informational, emotional, and tangible support from others. The second most common theme from our analysis was “giving advice” which we contextualized as referring to acts of service.…”
Section: Discussionmentioning
confidence: 99%
“…Natural experiments, including the COVID-19 pandemic, have reinforced the importance of social networks in aiding addiction and recovery [ 13 , 14 ]. Indeed, since the pandemic was declared a national emergency in February 2020, the Centers for Disease Control and Prevention (CDC) identified a 13% increase in licit and illicit substance use, abuse, and overdose compared with points prior to the pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%